The Role of Instrumental and Integrative Motivation in Student’s Achievement In Language Class of MAN I Malang - Luluk Machsufah (Language-Edu, 2019)
This study involved two of instruments, namely a student achievement and a questionnaire. The questionnaire was adopted from Gadner"AMTB and adjusted for participant understanding to collect data of the learners’ motivation. The data from a questionnaire were used to predict student motivation.   Based on the empirical evidence obtained,  the results of this study. Hypotesis one H1 states that Intrumental Motivation dan Integrative Motivation have significant positive influence to the Achievement. Hypothesis testing uses multiple regression analysis describe at the significance level of each X variable influences on the Y variable, toexplain that the hypothesis  is accepted . The result  shows that Intrumental Motivation has value ρ = 0,000 with regression coefficient of  0,400 dan Integrative Motivation has value ρ = 0,689 with regression coefficient 0,038, so hypotesis I accepted,clearly that it’s mean that faktor Intrumental Motivation factor and Integrative Motivation factor significantly has a positive influence on student achievement.  Instrumental Motivation and Integrative Motivation are jointly or individually gives a significant influence on the achievement of Language Class Students in MAN I Malang. From the two Instrumental Motivation research variables, the most influential (dominant), then it is necessary to increase Instrumental Motivation factors so that the student's achieve better achievements for students in MAN I Malang.